Discovery of Fusarium pseudograminearum Causing Crown Rot of Winter Wheat in Xinjiang Uygur Autonomous Region, China - Gao, Ying (Plant disease, 2024)
Fusarium pseudograminearum is an important plant pathogen that invades many crops (Zhang et al. 2018). Since it was first discovered in Australia in 1951, F. pseudograminearum has been reported in many countries and regions and caused huge economic losses (Burgess et al. 2001). In 2012, crown rot of wheat caused by F. pseudograminearum was discovered for the first time in Henan Province, China (Li et al. 2012). Wheat (Triticum aestivum L.) is one of the most important food crops in Xinjiang Uygur Autonomous Region (XUAR), with 1.07 million hectares cultivated in 2020. In June 2023, a survey of crown rot disease was carried out in winter wheat cv. Xindong 20 in Hotan area, XUAR, China (80.148907°E, 37.051474°N). About 5% of wheat plants showed symptoms of crown rot such as browning of the stem base and white head. The disease was observed in 85% of wheat fields. In order to identify the pathogens, 36 pieces of diseased stem basal tissue, 0.5 cm in length, were collected and sterilized with 75% alcohol for 30s and 5% NaOCl solution for 2 min, then rinsed three times with sterile water and placed on potato dextrose agar (PDA) medium at 25°C. A total of 27 isolates with consistent morphological characteristics were obtained using single-spore technique (Leslie and Summerell. 2006), and the isolation rate was 75%. The isolates grew rapidly on PDA, produced large numbers of fluffy white hyphae, and pink pigment accumulated in the medium. The isolates were grown on 2% mung bean flour medium and identified by morphological and molecular methods. Macroconidia were abundant, relatively slender, curved to almost straight, commonly two to seven septate, and averaged 22 to 72 × 1.8 to 4.9 μm. Microconidia were not observed. The morphological characters are consistent with Fusarium (Aoki and O'Donnell. 1999). Two isolates (LP-1 and LP-3) were selected for molecular identification. Primers EF1/EF2 (5'-ATGGGTAAGGARGACAAGAC-3'/5'-GGARGTACCAGTSATCATG-3') were used to amplify a portion of the EF-1α gene (O'Donnell et al. 1998). The two 696 bp PCR products were sequenced and submitted to GenBank. The EF-1α gene sequences (GenBank Accession No: PP062794 and PP062795) shared 99.9% identity (695/696) with published F.pseudograminearum sequences (e.g., OP105187, OP105184, OP105179, OP105173). The identification was further confirmed by F. pseudograminearum species-specific PCR primers Fp1-1/Fp1-2 (Aoki and O'Donnell. 1999). The expected PCR products of 518 bp were produced only in F. pseudograminearum. Pathogenicity tests of LP-1 and LP-3 isolates were performed on 7-day-old seedlings of winter wheat cv. Xindong 20 using the drip inoculation method with a 10-μl of a 106 macroconidia ml-1 suspension near the stem base (Xu et al. 2017). The experiment was repeated five times in a 20 to 25°C greenhouse. Control seedlings were treated with sterile water. After 4 weeks, wheat seedling death and crown browning occurred in the inoculated plants with over 90% incidence. No symptoms were observed in the control plants. The pathogen was reisolated from the inoculated plants by the method described above and identified by morphological and PCR amplification using F. pseudograminearum species-specific primers Fp1-1/Fp1-2. No F. pseudograminearum was isolated from the control plants, fulfilling Koch's postulates. To our knowledge, this is the first report of F. pseudograminearum causing crown rot of winter wheat in XUAR of China. Since F. pseudograminearum can cause great damage to wheat, one of the most important food crops in China, necessary measures should be taken to prevent the spread of F. pseudograminearum to other regions